Chemotherapy-induced acral erythema in leukemic patients: a report of 15 cases - (:unkn) unknown (BLACKWELL SCIENCE LTD, 1997)
Background Chemotherapy-induced acral erythema is a distinct localized cutaneous response to certain systemic chemotherapeutic agents. Methods Between January 1990 and December 1994, from a total of 76 leukemic patients who have received combination chemotherapy consisting of cytosine arabinoside and anthracycline antibiotics, 15 patients developed chemotherapy-induced acral erythema. Fourteen of the patients had acute myelocytic leukemia, and one of them had chronic myelogenous leukemia in blast phase. Clinical features of these 15 patients have been analysed. Biopsy specimens obtained from eight of the patients were also evaluated for histopathologic alterations. Results The overall incidence of this reaction was found to be 19.7% in our group of patients receiving this chemotherapy protocol. The onset of reaction Varied from the fourth to the seventeenth days of the chemotherapy and resolved within 2 weeks in most of the patients. Lesions appeared as well-defined erythema and edema involving the palmar surfaces in all of the patients. In nine of the patients the reaction recurred with subsequent chemotherapies. Scattered necrotic keratinocytes, vacuolar alterations of the basal layer, and mild to moderate perivascular lymphocytic infiltration in the dermis were the histopathologic findings observed in the biopsy specimens. Conclusions Chemotherapy-induced acral erythema is a frequent reaction in patients who are receiving high-dose chemotherapy. For patients in whom this self-limited condition develops, reassurance is the mainstay of therapy. Awareness of this reaction is also important to be able to differentiate it from acute graft Versus host disease in patients who receive bone marrow transplants.
Keywords: SKIN CHANGES